The optimal timing of evaluation of genebank accessions and the effect of biotechnology - Koo, Bonwoo; Wright, Brian D. (Wiley, 2000)
The lack of ex ante evaluation of germplasm in genebanks has been the single most prevalent and long‐standing complaint of plant breeders about the management of genebanks. Advances in biotechnology offer the possibility of faster, cheaper and more efficient evaluation methodologies. Will these new technologies favor ex post evaluation, as some expect, or will they lead to more ex ante evaluation? Will they also lead to earlier development of varieties with specific traits in anticipation of demand for them? Will the prospect of further advances in biotechnology favor delay of evaluation and development? This paper addresses these questions in the case of evaluation of germplasm for resistance to a disease.